"Do I have enough food?" How need for cognitive closure and gender impact stockpiling and food waste during the COVID-19 pandemic: A cross-national study in India and the United States of America. (1st January 2021) - Brizi, Ambra; Biraglia, Alessandro
Abstract: Food waste is considered to be one of the biggest issues affecting individuals around the globe. The COVID-19 pandemic, with the consequent lockdown processes, has recently triggered individuals to stockpile foodstuffs. Recent data shows, however, that individuals have not consumed a good proportion of the stockpiled food, resulting in increasing amounts of products ending up wasted. Using a cross-national survey conducted in the United States and India, we investigate how individuals' levels of need for cognitive closure (NFC) relate to food stockpiling and waste during the COVID-19 pandemic. Through a sequential mediation model, we show how individuals high in NFC did not perceive to have enough food at home, ending up buying more food than usual and, eventually, wasting more. Individuals' gender and country of residence moderate such phenomenon, with the effect being more pronounced among Indian (rather than American) women. We discuss how gender roles in different countries can correlate with the stockpiling and food waste processes. We conclude the manuscript by suggesting how public communication and policy making could develop targeted programs to mitigate such issues. Highlights: We study the effect of the COVID-19 pandemic on food stockpiling and waste. We conduct a cross-national survey in India and the United States. Individuals with high need for closure perceive having less food and stockpile more. A sequential mediation model shows how this process impacts food waste. Gender and country of residence moderate the mediation effect.